PENGARUH LATIHAN SHOOTING DENGAN SERVIS TINGGI TERHADAP KEMAMPUAN VOLLEY SHOOT PERMAINAN SEPAK BOLA PADA SISWA YANG IKUT EKSTRAKURIKULER SEPAKBOLA SMK NEGERI 1 PERANAP - Baba, Andres; Agust, Kristi; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was motivated by the results of observations conducted on the students' football extracurricular member SMK Negeri 1 Peranap. The results showed that the ability to launch an observation volley shoot unsatisfactory that are related in terms of both technical and physical. The aim of this study was simply the exercise effect shooting with a high service possible volley shoot of football on the football extracurricular students who participated determine SMK Negeri 1 Peranap. Researchers in this study proposed hypothesis is shooting exercise influence on the ability to service high volley shoot of football on the football extracurricular students who participated SMK Negeri 1 Peranap. This type of research experiments. The location of this study is planned on a football field near SMK Negeri 1 Peranap. The timing of the March in May 2016. The population conducted in this study, all members of extracurricular student in SMK Negeri 1 Peranap total of 16 students. The sample in this study is the entire population of 16 people or students. The tests used in this study test shoot bursts. T-test calculation results obtained t value at 4.36. The value is then compared with the value table t. T table at n = 16 or df = 15 at the level of 5% error is 02:13. the results of the comparison between any value t with t the value table as follows: 4.36> 2:13. Based on the above equation is known that the alternative hypothesis, which says that there is considerable practice shooting with high maintenance of the possibility volley shoot of football on the football extracurricular students who participated SMK Negeri 1 Peranap acceptableKeyword: practice shooting with a high serve, volley shoot, football